PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI STRES KERJA SEBAGAI VARIABEL INTERVENING STUDI PADA PT. TELKOM INDONESIA WITEL SURABAYA - DWI PRAYOGO, BAGUS (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to determine whether organizational culture has an influence on employee performance through work stress as an intervening variable. The analysis used is descriptive analysis by determining the sample using probability sampling techniques, obtained 146 employees from a total of 231 employees of PT. Telkom Indonesia Witel Surabaya using SEM AMOS analysis tool. The results of this study indicate that organizational culture has a positive effect on employee performance, the better the organizational culture applied by the company, the better the performance of employees and vice versa. Organizational culture has a positive effect on work stress, the better the organizational culture that is applied by the company, the tendency of employees to become stressed increases. Job stress does not affect employee performance, stress perceived by employees does not affect performance. Job stress does not mediate organizational culture on employee performance.